Analytical model for the strain analysis of continuous buried pipelines in geohazard areas. (1st December 2017) - Sarvanis, Gregory C.; Karamanos, Spyros A.
Highlights: Novel analytical solution for buried pipelines under permanent ground deformations. Closed-form expressions for calculating pipeline deformation and strains. Very good comparison with numerical finite element solutions. Simple and efficient tool for pipeline preliminary design against geohazard actions. Abstract: In geohazard areas, buried pipelines are subjected to permanent ground-induced deformations, which constitute major threats for their structural safety. Geohazards include seismic fault movement, liquefaction-induced lateral spreading, slope instability or soil subsidence, and are associated with the development of severe strains in the pipeline. Calculation of these strains is necessary for assessing pipeline integrity. In the present paper, an analytical methodology is presented that allows for simple and efficient pipeline strain analysis in geohazard areas. The methodology is compared with existing more elaborate analytical methodologies and finite element predictions. The analytical formulation results in closed form expressions and the model contributes to better understanding of buried pipeline behavior subjected to permanent ground-induced deformations. The proposed methodology is directly applicable to fault actions, but it can be also applicable to a wide range of geohazards. Furthermore, using this methodology, one may predict the strains developed in the pipeline wall due to ground-induced actions in a simple and efficiently manner and is suitable for the preliminary design of pipelines.